2002
DOI: 10.1212/wnl.59.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural abnormalities in young children with autism spectrum disorder

Abstract: These structural findings suggest abnormal brain developmental processes early in the clinical course of autism. Research currently is underway to better elucidate mechanisms underlying these structural abnormalities and their longitudinal progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
658
5
28

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 840 publications
(746 citation statements)
references
References 39 publications
55
658
5
28
Order By: Relevance
“…Neuroanatomical observations, along with data from functional magnetic resonance imaging, have shown that a major pathological hallmark in autistic individuals may be a premature brain overgrowth affecting structures such as the cerebral cortex, the limbic system, including the hippocampal formation and the amygdala, and the cerebellum (Courchesne et al, 2001(Courchesne et al, , 2003Sparks et al, 2002;Schumann et al, 2004). Such overgrowth would happen early before clinical diagnosis is made consistent with the possibility that growth factors, which normally regulate cell differentiation, proliferation and survival, having a functional role in the disease.…”
Section: Wnt Signaling and Autismmentioning
confidence: 93%
“…Neuroanatomical observations, along with data from functional magnetic resonance imaging, have shown that a major pathological hallmark in autistic individuals may be a premature brain overgrowth affecting structures such as the cerebral cortex, the limbic system, including the hippocampal formation and the amygdala, and the cerebellum (Courchesne et al, 2001(Courchesne et al, , 2003Sparks et al, 2002;Schumann et al, 2004). Such overgrowth would happen early before clinical diagnosis is made consistent with the possibility that growth factors, which normally regulate cell differentiation, proliferation and survival, having a functional role in the disease.…”
Section: Wnt Signaling and Autismmentioning
confidence: 93%
“…Whereas earlier postmortem studies on autistic patients indicated an increased number of cells with reduced cell size in the cortical, medial, and central nuclei of the amygdala (Kemper and Bauman, 1998), more recent and modern stereological counts of neurons in the amygdala revealed a reduced number of neurons, particularly in the lateral nucleus (Schumann and Amaral, 2006). The total amygdala volume is enlarged during early infancy (Sparks et al, 2002;Schumann et al, 2004), but can be reduced in adulthood (Aylward et al, 1999). Functionally, the amygdala has been linked to autism through its involvement in socio-emotional behavior.…”
Section: Introductionmentioning
confidence: 89%
“…Both microscopic and macroscopic studies reveal alterations in the morphology of the amygdala in autism (Kemper and Bauman, 1998;Aylward et al, 1999;Sparks et al, 2002;Schumann et al, 2004;Schumann and Amaral, 2006), indicating a dysfunction in this region that might possibly contribute to the autistic pathology. The current 'amygdala theory of autism' is based on the lost capability to evaluate socioemotional information and lost drive for social interaction derived from lesioning studies in monkeys and a few functional imaging studies in humans (Baron-Cohen et al, 2000;Sweeten et al, 2002;Pelphrey et al, 2004;Bachevalier and Loveland, 2006;Schultz, 2005), which implies that a hypofunctioning amygdala underlies autism.…”
Section: A Novel Role Suggested For the Amygdala In Autismmentioning
confidence: 99%
“…Also, structural MRI studies suggest abnormalities in the development of the amygdala in ASD. Initial reports were contradictory, showing evidence for smaller [217], larger [218,219] and equivalent [220] amygdala volumes in subjects with ASD compared to controls. However, more recent data suggest an unusual developmental time course for the amydala in ASD, in which the amydala is larger in children with ASD (ages 7.5 to 12.5 years old) compared to several control groups, whereas no differences are detectable between adolescents with ASD versus controls [221].…”
Section: Impairments Of Facial Expression Recognition In Asdmentioning
confidence: 97%